Monthly electricity usage at Australian Antarctic Stations - BONNICE, JEREMY (hasPrincipalInvestigator); RATCLIFFE, GUY (processor); SHEERS, ROBERT (processor); Australian Antarctic Data Centre (publisher)
These data are no longer archived in the Australian Antarctic Data Centre. These data cover a period of January 1993 to February 2016. INDICATOR DEFINITION The amount of electricity (kWh) used at Casey, Davis, Mawson and Macquarie Island stations as measured on a monthly basis and reported in the monthly reports from the Station Plant Inspectors to the Kingston (Head Office) Mechanical Supervisor. TYPE OF INDICATOR There are three types of indicators used in this report: 1.Describes the CONDITION of important elements of a system; 2.Show the extent of the major PRESSURES exerted on a system; 3.Determine RESPONSES to either condition or changes in the condition of a system. This indicator is one of: PRESSURE RATIONALE FOR INDICATOR SELECTION The amount of electricity used at a station is a reflection of the efficiency of various electrical and systems and the amount of fuel used to generate this electricity. The amount of fuel used in Antarctica for electricity generation is proportional to environmental impact due to the emissions. The electricity usage of the station provides an indication of the relative need for electrical power compared with the thermal load of the station. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic stations: Casey (lat 66 deg 16' 54.5& S, long 110 deg 31' 39.4& E), Davis (lat 68 deg 34' 35.8& S, long 77 deg 58' 02.6& E), Mawson (lat 67 deg 36' 09.7& S, long 62 deg 52' 25.7& E) and Macquarie Island (lat 54 deg 37' 59.9& S, long 158 deg 52' 59.9& E). Frequency: Monthly reports Measurement technique: The figures are obtained by direct reading of gauges on the stations on a regular basis. The data are recorded in the Plant Inspectors monthly reports. RESEARCH ISSUES In the future, it is planned to automate the collection of most of this data. LINKS TO OTHER INDICATORS SOE Indicator 1 - Monthly mean air temperatures at Australian Antarctic stations. SOE Indicator 2 - Highest monthly air temperatures at Australian Antarctic Stations SOE Indicator 3 - Lowest monthly air temperatures at Australian Antarctic Stations SOE Indicator 4 - Monthly mean lower stratospheric temperatures above Australian Antarctic Stations SOE Indicator 47 - Number and nature of incidents resulting in environmental impact SOE Indicator 48 - Station and ship person days SOE Indicator 56 - Monthly fuel usage of the generator sets and boilers